2016
DOI: 10.3390/ijms17122101
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Injury: Stem Cell Therapy and Peripheral Nerve Transfer

Abstract: Peripheral nerve injury can lead to great morbidity in those afflicted, ranging from sensory loss, motor loss, chronic pain, or a combination of deficits. Over time, research has investigated neuronal molecular mechanisms implicated in nerve damage, classified nerve injury, and developed surgical techniques for treatment. Despite these advancements, full functional recovery remains less than ideal. In this review, we discuss historical aspects of peripheral nerve injury and introduce nerve transfer as a therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
136
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 72 publications
(100 reference statements)
1
136
0
4
Order By: Relevance
“…In contrary, functional recovery occurred from week 8 to week 16 in CHIT/MP supporting again this idea that selection of an appropriate method to evaluate functional recovery is crucial. This study also supported the idea that the walking track analysis (SFI) is more comprehensive and reliable than histomorphometric methods in peripheral nerve repair studies [25,28].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In contrary, functional recovery occurred from week 8 to week 16 in CHIT/MP supporting again this idea that selection of an appropriate method to evaluate functional recovery is crucial. This study also supported the idea that the walking track analysis (SFI) is more comprehensive and reliable than histomorphometric methods in peripheral nerve repair studies [25,28].…”
Section: Discussionsupporting
confidence: 64%
“…Castaneda et al, [25] suggested that arrival of sprouts from the proximal stump at the distal nerve stump does not necessarily imply recovery of nerve function. Walking track analysis has frequently been used to reliably determine functional recovery following nerve repair in rat models [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In cell-based therapies, neural crest cells are the main source of Schwann cells. SC seeds transplanted in a nerve conduit enhance axonal regeneration, but SC seeds have some disadvantages such as slow expansion to large numbers and being hard to obtain [129,130,140]. As a result, ideal cells to be used for neural regeneration should have the properties of being suitable for easy harvesting, not requiring immunosuppression, being able to integrate to the injury site and being non-tumorigenic.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Schwann cell cultures have mostly shown acceptable results in experimental studies; however, they are not good enough and search for an ideal cell is still ongoing. Bone marrow-derived mesenchymal cells have also demonstrated favourable results with numerous advantages like easy harvesting, high cell viability and secretion of multiple trophic factors [139,140].…”
Section: Cell-based Therapymentioning
confidence: 99%
See 1 more Smart Citation